Peningkatan Nilai Tambah Usaha Olahan Keripik Pisang di Desa Tenajar, Kabupaten Indramayu, Jawa Barat - . Hartoyo; Sutrisno Koswara; . Sulassih (Institut Pertanian Bogor, 2019)
The objectives of this community service activity are to: 1) Increase knowledge and skills in processing banana chips through training for community groups in the Pesantren (Islamic Boarding School) of Syubbanul Yaum, Tenajar Village, and 2) Analyze the added value of banana chips processing. The activities were carried out during July–September 2019 (3 months) with several activities that began with preparation, training on making banana chips, and technical assistances. The results of the training activities showed that there were knowledge improvement of training participants in terms of: selection the quality of material (by 63.16), innovation in the form of banana chips (by 89.47), and innovation in the taste of banana chips (by 26.32). The skills of participants have been improved to apply innovation in the terms of form and flavor of banana chips. The innovations in the form of chips include; wasp nests, elongated, sloped, rounded, jagged and rounded jagged, while flavored innovations include; cheese, chocolate, green tea, palm sugar, spicy and savory. The ability of participants to make banana chips with a thickness of 1–2 mm was increased by 26.32 by using various shapes of knives. The result of value added analysis shows that the processing of banana chips can provide economic added value of IDR 8,000/kg with a value added ratio of 53.30% of the sales value. The profit of banana chips business reached IDR 5,200/kg with a profit ratio of 65%. There is, therefore, the processing of banana chips is a suitable business for community groups in managing Pesantren to foster the economic independence of Pesantren and village communities.